2023
DOI: 10.3390/vaccines11040745
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Factors Associated with COVID-19 Vaccination among People in Guatemalan Municipalities

Abstract: The Republic of Guatemala’s reported COVID-19 vaccination coverage is among the lowest in the Americas and there are limited studies describing the disparities in vaccine uptake within the country. We performed a cross-sectional ecological analysis using multi-level modeling to identify sociodemographic characteristics that were associated with low COVID-19 vaccination coverage among Guatemalan municipalities as of 30 November 2022. Municipalities with a higher proportion of people experiencing poverty (β = −0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Though health centers are commonly situated in the area and can be reached in 24 minutes by walk, most respondents lamented that most of these community health facilities lack adequate medical supplies and are not available for consultation. [26] found that rural poverty, indigenous ancestry, and issues with healthcare access are significantly associated with low COVID-19 vaccination rates. In Occidental Mindoro, 21% of the households interviewed lack at least one COVID-19 vaccinated member.…”
Section: Incidence Of Deprivation Among Farming Householdmentioning
confidence: 98%
“…Though health centers are commonly situated in the area and can be reached in 24 minutes by walk, most respondents lamented that most of these community health facilities lack adequate medical supplies and are not available for consultation. [26] found that rural poverty, indigenous ancestry, and issues with healthcare access are significantly associated with low COVID-19 vaccination rates. In Occidental Mindoro, 21% of the households interviewed lack at least one COVID-19 vaccinated member.…”
Section: Incidence Of Deprivation Among Farming Householdmentioning
confidence: 98%
“…The Special Issue features research, reviews, and commentaries that span a range of immunization topics and populations. While there is an emphasis on childhood vaccinations [ 15 , 16 , 17 , 18 ]—exploring inequalities in DTP and measles-containing vaccine (MCV) coverage [ 19 , 20 , 21 , 22 , 23 ] and patterns of inequality in unvaccinated or zero-dose children [ 24 , 25 , 26 , 27 , 28 , 29 ]—contributions also cover inequalities in adult immunization [ 30 ], including protection of pregnant women and their newborns against tetanus [ 31 ] and COVID-19 vaccination [ 32 , 33 ].…”
Section: The Special Issue: Monitoring Inequalities and Understanding...mentioning
confidence: 99%
“…An encouraging observation while putting together this Special Issue has been the use of a variety of data sources to assess immunization inequalities. Studies have made use of traditional sources of immunization data like administrative data [ 19 , 23 , 32 ] and population surveys [ 18 , 21 , 22 , 27 , 29 , 30 ] (including Demographic and Health Surveys and/or Multiple Indicator Cluster Surveys [ 15 , 20 , 31 ]), while several other studies explored the potential of novel sources such as geospatial data [ 24 , 25 ], electronic immunization registries [ 34 ], dialogues [ 16 ], country appraisals and reports [ 35 ], and funding proposals [ 26 ]. Three review studies relied on synthesis and structured analyses drawing from a multitude of existing studies [ 17 , 33 , 36 ].…”
Section: The Special Issue: Monitoring Inequalities and Understanding...mentioning
confidence: 99%
See 1 more Smart Citation